A study on tourists’ feedback and satisfaction on Langkawi nature and ecotourism industry / Mohammad Zaki Ayob ...[et al.] - Ayob, Mohammad Zaki; Mohd Saman, Fatimah; Hussin, Zaliha; Md Hashim, Azhari (Research Management Institute, 2008)
Ecotourism is fast becoming a revenue generator for many developing countries. These countries are progressively becoming competitive. This study is directed towards identifying factors contributing to tourists’ satisfaction, and these include business management and systems, ethics, marketing, and environmental management. Sampling design was non-probability due to absence of sampling frames. Data was collected from sample subjects at jetty points when tourists were about to exit the tour party. Structural Equations Modelling (SEM) was utilized to test four differing conceptual models. The Baseline Comparisons, Parsimony Adjusted Measures, and the RMSEA were used to evaluate good model fit. It was found that Model 3 fulfilled the descriptive fit statistics requirements for good model fit. The overall tourists’ satisfaction was also calculated and found to be 79.1 of a possible 100 points, only short by 0.9 points from being excellent. In terms of important factors, it was found that marketing practices influenced 42.1 percent, business ethics 23.9 percent, environmental management 14.5 percent, and business management and operational systems 7.8 percent towards tourists’ satisfaction respectively. Important elements in marketing practices include the need to provide sufficient equipment, constantly providing tips to tourists for maximum enjoyment, and spending more than 75 percent of ecotourism activities in the natural area. Important elements in business ethics include consistently addressing tourists’ safety, and providing ecotourism service in the best possible way. Crucial elements in environmental management include prevention of irreversible danger to nature and provision towards minimal disturbance to wildlife. In business management and operational systems, important elements include safety measures and effective operational procedures. Specific elements requiring improvements include service delivery, service value for money, exceeding tourists’ expectations, providing relevant facilities, adequate transportation, helping tourists to experience nature, preventing damage to the environment, effective garbage and waste management, customer service, product maintenance, and observing operational procedures.